A Brief Report on a Systematic Review of Real-World Effectiveness Studies of ICS/LAMA/LABA for Treatment of Adults with Asthma in the US - Stephen G. Noorduyn; Kejsi Begaj; Amber Martin; Sergio Forero-Schwanhaeuser; Kassandra Schaible; Alison Moore; Rosirene Paczkowski (Pulmonary Therapy)
Abstract Introduction Long-acting muscarinic antagonist (LAMA) addition to inhaled corticosteroid/long-acting β2-agonist (ICS/LABA) dual therapy is recommended for severe asthma, but its real-world effectiveness is not well established. Methods A systematic literature review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to investigate clinical outcomes in US adults with asthma receiving ICS + LABA + LAMA as multiple-/single-inhaler triple therapy (MITT/SITT). Real-world/observational studies published in English in Embase/MEDLINE databases (2014–2024) and conference abstracts presented 2022–2024 were eligible for inclusion. Results From 588 identified records, only 8 articles reporting 6 unique studies were included; 2 assessed SITT and 4 assessed MITT, and 4 treatments were investigated. Exacerbation rates reported in two studies were significantly reduced with tiotropium (TIO) + ICS + LABA MITT versus high-dose ICS + LABA within 6 (64% lower) and 12 months (73%), and fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100/62.5/25 mcg SITT versus pre-treatment after 12 months (41%). Oral corticosteroid (OCS) use was reported in two studies. The proportion of patients with ≥ 1 rescue OCS dispensing decreased with TIO 1.25 mcg + ICS + LABA MITT, with greatest reductions for MITT ± leukotriene receptor antagonist (pre-treatment: 68.4%, post treatment: 54.2%). Mean number of OCS dispensings/patient/year significantly decreased (29%, p < 0.001) following FF/UMEC/VI 100/62.5/25 mcg SITT initiation. Treatment adherence/persistence was reported in three studies. Mean (standard deviation) proportion of days covered was significantly higher (p < 0.001) for FF/UMEC/VI SITT versus MITT after 6 (0.56 [0.31] versus 0.46 [0.31]) and 12 months (0.46 [0.33] versus 0.35 [0.30]). Persistence at 12 months was 25.9% and 12.0%, respectively. Lung function, clinical remission, quality of life, and safety outcomes were not reported in any study. Conclusions This brief communication reports a systematic review that identified few sources of SITT or MITT in US patients with asthma. Although inclusion of observational studies can result in reporting/selection bias, we identified greater clinical benefits with triple therapies versus dual therapies.